Pelatihan Pengajaran Bahasa Arab bagi Guru Bahasa Arab di MI Quhas Primary School Dar Al-Masaleh Jambi - Firman Firman; Friscilla Wulan Tersta; Fellicia Ayu Sekonda; Hidayatul Arief; Mar'atun Sholiha; Sahrizal Vahlepi (Pusat Pengabdian Masyarakat (PPM) Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam Negeri (IAIN) Metro, 2022)
Arabic education is a very important education, especially in the MI Quhas Primary School Dar Al-Masaleh Jambi. English must be approved by a teacher who has English competence. To improve the quality of learning Arabic in the Mi Quhas Primary School Dar Al-Masaleh Jambi, the first central goal to be addressed is the quality of teachers. This can be done through increasing understanding of learning concepts through training, and increasing the competence of Arabic language teachers. This beacuse teacher has a role in assiting the students in learning. The training and dedication efforts was undertaken by the team leacturer of Arabic language education. It was hope that this activity can help Arabic teachers to have some abilities in Arabic education at the MI Quhas Primary School Dar Al-Masaleh Jambi which can improve the quality of language learning arabic as proven by supporting arabic learning outcomes for students.